Cloning, sequence and mRNA expression of bovine interleukin-16 - Mertens, B.; Bishop, Richard P.; Taracha, E.A.; Morzaria, S.P.; Nene, Vishvanath M.; Savadye, D. (Informa UK Limited, 2000)
A lambda gtll cDNA library was constructed using mRNA isolated from Theileria parva-infected bovine lymphocytes. Sequencing of random clones of this library resulted in the identification of a cDNA encoding bovine interleukin-16 (IL-16). The cDNA has an open reading frame of 1134 bp, and a 3? untranslated region of 275 nucleotides with a polyadenylation signal 16 bases upstream from the poly (A) tail. The protein predicted by the cDNA sequence contains 378 amino acids and the level of amino acid homology with the corresponding part of human precursor IL-16 is 79%. No information is available about the tissue distribution of IL-16 in cattle, therefore we investigated the expression of IL-16 mRNA in bovine lymphoid tissues by reverse-transcription polymerase chain reaction assays. To investigate the potential of IL-16 as an immunoregulatory molecule we also analysed IL-16 mRNA expression in CD4+ and CD8+T-cell clones derived from T. parva-immunised cattle.